Tele-Health Psychological Interventions in Breast Cancer at the Time of Coronavirus: A Narrative Review - Bertolucci, Ilaria (Journal of Psychology and Psychotherapy Research, 2023)
Introduction: During the recent pandemic-related health emergency of COVID-19, the health system care has undergone several substantial and sudden changes to benefit the populations of patients affected by COVID-19 delaying the diagnosis and treatment of all other patients. One of the most vulnerable populations during this period was the oncological population. The use of telemedicine has become necessary to compensate for all this by forging medical and psychological support at a distance. Objectives: The purpose of this narrative review is to offer an overview of the literature on present scientific papers regarding tele-health psychological interventions aimed at breast cancer patients during the pandemic period of COVID-19 and discussing the reported effects. Methods: This narrative review has been realized through a revision of the scientific literature conducted from August to October 2023 using the following electronic databases: “PubMed”, “Science Direct” and “Google Scholar” typing keywords related to the pandemic period, breast cancer population and telehealth psychological interventions. For the evaluation of the effects of the interventions, the statistical indices of p-value and effect size measures were considered. Results: Online mindfulness-based interventions have been found to be significant in reducing anxiety, depression and sleep problems, and in improving self-perception of body image, quality of life, and self-efficacy. No significant results are detected in the reduction of depression symptoms and stress levels between groups. Discussions: Very limited studies investigated the topic. Further research is needed to better understand the efficacy of telepsychology during the pandemic period and deepen research in terms of other therapeutic approaches and other methods of treatment delivery. In addition, interventions based on a systemic approach, that involve both health care workers and caregivers, can be more effective for the overall well-being of breast cancer patients.